A conservation framework for the Critically Endangered endemic species of the Caribbean palm Coccothrinax. Issue 3 (19th September 2017) - Jestrow, Brett; Peguero, Brígido; Jiménez, Francisco; Verdecia, Raúl; González-Oliva, Lisbet; Moya, Celio E.; Cinea, William; Griffith, M. Patrick; Meerow, Alan W.; Maunder, Mike; Francisco-Ortega, Javier
Abstract: With 30 threatened species (14 categorized as Critically Endangered and 16 as Endangered, sensu IUCN), Coccothrinax (c. 54 species) is the flagship palm genus for conservation in the Caribbean Island Biodiversity Hotspot. Coccothrinax has its centre of taxonomic diversity in these islands, with c. 51 endemic species. We present a conservation framework for the 14 Critically Endangered species, found in Cuba, Haiti or the Dominican Republic. Only two species ( C. jimenezii, C. montana ) occur in more than one country (Haiti and the Dominican Republic). Immediate threats include oil drilling and nickel mining, intrusion of saline water into soil, urban and agricultural development, low population recruitment, uncontrolled fires, interspecific hybridization, and unsustainable ethnobotanical practices. Coccothrinax bermudezii, C. borhidiana, C. crinita ssp. crinita, C. leonis and C. spissa are not conserved in protected areas. Coccothrinax bermudezii, C. jimenezii, C. leonis and C. nipensis are not part of ex situ collections. Based on results from a conservation project targeting C. jimenezii, we recommend international cooperation between the three range states to implement integrative conservation management plans, plant exploration initiatives, taxonomic revisions, outreach, and fundraising. The ultimate aim of this review is to provide baseline information that will develop conservation synergy among relevant parties working on Coccothrinax conservation in Cuba, Haiti and the Dominican Republic. Such collaborations could also benefit through partnerships with botanists working in other countries.